Transferrin receptor 2 is a potential novel therapeutic target for β-thalassemia: evidence from a murine model - Artuso, Irene; Lidonnici, Maria Rosa; Altamura, Sandro; Mandelli, Giacomo; Pettinato, Mariateresa; Muckenthaler, Martina; Silvestri, Laura; Ferrari, Giuliana; Camaschella, Clara; Nai, Antonella (Blood, 2018)
Key Points. Deletion of BM Tfr2 ameliorates anemia and iron overload in a murine model of transfusion-independent thalassemia.Deletion of Tfr2 enhances transcr